Effect of Alternative Palatal Root Access Technique on Fracture Resistance of Root Canal Treated Maxillary Fourth Premolar Teeth in Dogs - Matelski, Jennifer; Rendahl, Aaron; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2020)
A biomechanical study was performed to identify the effect of different treatment methods for difficult to instrument palatal roots on the fracture resistance of root canal treated maxillary fourth premolar teeth in dogs. Forty maxillary fourth premolar teeth with surrounding alveolar bone were harvested from beagle cadavers. Inclusion criteria included maxillary fourth premolars with no evidence of disease and similar distal root canal volumes on radiographic evaluation. The teeth were randomly divided into a control group and three treatment groups based on the endodontic treatment technique for the palatal root. The control group had a single 2mm transcoronal access on the mesiobuccal aspect of the tooth to allow instrumentation of both the mesiobuccal and palatal root through a single small access. Alternative treatment modalities that are described for difficult to instrument palatal roots investigated in this study included enlarging the transcoronal mesiobuccal access to 4 mm, making an additional access directly over the palatal root (2 mm), and hemisection with extraction of the palatal root. All teeth had the same distal root access size (2mm) and relative location. After access, all teeth were filed, shaped, obturated, and restored in the same fashion. Axial compression testing was performed at an angle of 60 degrees to the long axis of the tooth using a universal materials testing machine. The maximum force prior to fracture was determined for each tooth based on a force versus deflection curve. The mean maximum force prior to fracture for all teeth was 831N. No significant difference in fracture resistance was identified between the control group and treatment groups or between the different treatment groups themselves. Thus, when faced with a difficult to instrument palatal root, the treatment method chosen should be based on operator preference and experience.